A Cross-Cultural Analysis of Family Education in China and the U.S.: Home with Kids vs. Good Luck Charlie - Yifan Zhao (Journal of Linguistics and Communication Studies, 2025)
Family education serves as the foundation of social education and plays a decisive role in shaping children’s worldview, values, and outlook on life. As a crucial component of the social education system, family education not only exerts an indelible and permanent influence on the development of lifelong habits in children but also directly impacts the stability and development of future society. This paper, grounded in the theory of cultural dimensions, analyzes the differences in existing educational philosophies between China and the United States by considering various factors such as cultural backgrounds and social values. The aim is to integrate the essence of educational philosophies from both countries to propose several suggestions for improving current family education practices in China.